Little Randall-Sundrum models [epsilon]K strikes again - Bauer, Martin; Neubert, Matthias (Physical review. D, Particles, fields, gravitation, and cosmology, 2009)
A detailed phenomenological analysis of neutral kaon mixing in “little Randall-Sundrum” models is presented. It is shown that the constraints arising from the CP-violating quantity ϵK can, depending on the value of the ultraviolet cutoff, be even stronger than in the original Randall-Sundrum scenario addressing the hierarchy problem up to the Planck scale. The origin of the enhancement is explained, and a bound ΛUV>several 103 TeV is derived, below which vast corrections to ϵK are generically unavoidable. Implications for nonstandard Z0→b¯b couplings are briefly discussed.
Im Titel ist "K" tiefgestellt
Gesehen am 21.11.2017